Anti-Italianism in sixteenth-century France - Heller, Henry (University of Toronto Press, 2003)
In an examination of the Italian presence in France under the Valois and Bourbon monarchs, Heller links the cultural, moral, and political aspects of anti-Italianism with the rise of economic nationalism among the emergent French middle class.